2004
DOI: 10.1124/mol.65.5.1225
|View full text |Cite
|
Sign up to set email alerts
|

Oral Exposure to Benzo[a]pyrene in the Mouse: Detoxication by Inducible Cytochrome P450 Is More Important Than Metabolic Activation

Abstract: The cytochrome P450 (CYP1A1) enzyme metabolically activates many polycyclic aromatic hydrocarbons, including benzo [a]pyrene (BaP), to DNA-and protein-binding intermediates that are associated with toxicity, mutagenesis, and carcinogenesis. As a result, it is widely accepted that CYP1A1 potentiates the toxicity of this class of chemicals. In distinct contrast, we show here that CYP1A1 inducibility is essential in the detoxication of oral BaP. We compared Cyp1a1(Ϫ/Ϫ) knockout mice, having the genetic absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
266
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(290 citation statements)
references
References 53 publications
23
266
1
Order By: Relevance
“…Furthermore, considering AAIa was much less cytotoxic and mutagenic than AAI [14,32] , we speculate that the formation of AAIa by CYP1A plays a role in detoxicification of AAI in vivo in contrast to its toxicity in vitro. The discrepant roles of CYP1A in vivo and in vitro have been shown before [33][34][35] and our study supports that CYP1A is cytoprotective rather than cytotoxic in vivo [36] .…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, considering AAIa was much less cytotoxic and mutagenic than AAI [14,32] , we speculate that the formation of AAIa by CYP1A plays a role in detoxicification of AAI in vivo in contrast to its toxicity in vitro. The discrepant roles of CYP1A in vivo and in vitro have been shown before [33][34][35] and our study supports that CYP1A is cytoprotective rather than cytotoxic in vivo [36] .…”
Section: Discussionsupporting
confidence: 75%
“…We found however that the levels of dG-N 2 -BPDE adducts in livers of these mice treated with BaP were higher than in WT mice (Arlt et al, 2008;. Therefore, these and other factors such as: (i) detoxification of reactive BaP metabolites by both phase I and phase II enzymes (conjugation), (ii) rate of repair of BaP-DNA adducts, and (iii) BaP-induced expression of genes of enzymes involved in BaP detoxification or in DNA damage response (Uno et al, 2004;, might also influence BaP-DNA adduct levels in vivo. However, the impacts of those factors on BaP-DNA adduct formation in the present study in vivo remain to be explored.…”
Section: Resultsmentioning
confidence: 87%
“…CYP1A1-null mice died within 30 days after oral administration of 125 mg/kg bw benzo [a]pyrene, while wild-type mice did not show any signs of toxicity for 1 year. In addition, benzo [a]pyrene-DNA adduct levels were found to be higher in CYP1A1-null mice than in the wild-type mice (Uno et al, 2004;Nebert, 2005a).…”
Section: Drug-metabolizing Enzymes Involved In the Metabolism Of Pahsmentioning
confidence: 98%
“…Recently, Uno et al (2004) showed that CYP1A1 is important in the detoxification and protection against the oral toxicity of benzo [a]pyrene rather than in its metabolic activation in studies using CYP1A1 knockout mice. CYP1A1-null mice died within 30 days after oral administration of 125 mg/kg bw benzo [a]pyrene, while wild-type mice did not show any signs of toxicity for 1 year.…”
Section: Drug-metabolizing Enzymes Involved In the Metabolism Of Pahsmentioning
confidence: 99%